Choice of playing roles of the midfielders and moving forwards in female water polo. - Olga Pilipko; Alina Pilipko; Volodymyr Ashanin (Kharkiv State Academy of Physical Culture, 2020)
Purpose: to develop and experimentally substantiate the method of choosing the game role of the midfielders and moving forwards in female water polo. Material and methods: analysis and generalization of literary sources, pedagogical observation, anthropometric and physiological measurements, testing of swimming performance, special and technical training, analysis of the game activities of water polo players using test game protocols, methods of mathematical statistics. The contingent of the surveyed were members of the team of the Kharkiv region on the female water polo. Results: the authors determined the features of the structure of special preparedness of qualified female water polo players who perform functions as midfielders and moving forwards, investigated the relationship between physical development indicators, technical and special swimming training and efficiency of game actions спортсменок даного амплуа, developed model characteristics of the most significant parameters of the structure of special preparedness of qualified female water polo players, which can serve as reference points to determine game role of the midfielders and moving forwards. Conclusions: the definition of playing roles in women's water polo should be based on a comprehensive analysis of indicators that reflect different aspects of preparedness of qualified sportswomen.